Investigating Employment Delays: A Multiple Classification Analysis of Job Search Duration among Graduates in Islamic Community Development - Afifah, Puspa Nur; Rahmadhani, Nadya; Rifqi, Syehabu (KUBIK, 2024)
Indonesia is facing big challenges: an overabundance of graduates and limited job prospects. In February 2022, the central statistics agency provided a clear picture, more than 13 million people have a bachelor's degree in Indonesia and the number of unemployed is 8.4 million people. Banten Province is ranked first in the unemployment rate in Indonesia, namely 8.53%. The aim of this research is to determine the factors that influence the length of job search for graduates of the Islamic Community Development Program at UIN Sultan Maulana Hasanuddin Banten. The analytical method used is Multiple Classification Analysis (MCA), this research investigates the influence of variables, such as gender, length of study, GPA, organizational experience, academic achievement, work experience, employment sector, and foreign language proficiency. The research results show that there is a significant relationship between length of study, GPA, work experience, and length of job search. The ANOVA test shows that these three variables have a low significance level (